ORTHOEPIC COMPETENCE AS A HIGH-VALUE COMPONENT OF SPEECH CULTURE (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes orthoepic competence as a significant component of students’ speech culture in the process of studying Russian. Drawing on the source conference material, the paper interprets orthoepic competence as the integrated ability to observe pronunciation norms, use stress correctly, maintain clear diction, and coordinate phonetic, intonational, and communicative features of speech in accordance with the goals and conditions of interaction. The study argues that the formation of such competence is not a narrow technical task but an essential element of professional preparation, because insufficiently normative speech negatively affects perception, credibility, organizational interaction, and the overall quality of communication. Special attention is given to the causes of pronunciation errors among students in non-Russian-speaking educational environments: dialect influence, entrenched accent patterns, the impact of colloquial and media speech, weak self-monitoring, incomplete knowledge of norms, and difficulties connected with the articulatory apparatus. The article also identifies the pedagogical implications of these factors and substantiates the need for systematic, staged, and communicatively oriented orthoepic work. It is concluded that the formation of orthoepic competence strengthens speech culture, improves professional communication, and supports the broader linguistic development of future specialists.